Methanogenic biodegradation of C9 to C12 n-alkanes initiated by Smithella via fumarate addition mechanism - Jia-Heng Ji; Lei Zhou; Serge Maurice Mbadinga; Muhammad Irfan; Yi-Fan Liu; Pan Pan; Zhen-Zhen Qi; Jing Chen; Jin-Feng Liu; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (AMB Express, 2020)
Abstract In the present study, a methanogenic alkane-degrading (a mixture of C9 to C12 n-alkanes) culture enriched from production water of a low-temperature oil reservoir was established and assessed. Significant methane production was detected in the alkane-amended enrichment cultures compared with alkane-free controls over an incubation period of 1 year. At the end of the incubation, fumarate addition metabolites (C9 to C12 alkylsuccinates) and assA genes (encoding the alpha subunit of alkylsuccinate synthase) were detected only in the alkane-amended enrichment cultures. Microbial community analysis showed that putative syntrophic n-alkane degraders (Smithella) capable of initiating n-alkanes by fumarate addition mechanism were enriched in the alkane-amended enrichment cultures. In addition, both hydrogenotrophic (Methanocalculus) and acetoclastic (Methanothrix) methanogens were also observed. Our results provide further evidence that alkanes can be activated by addition to fumarate under methanogenic conditions.